Perempuan dan Kearifan Lokal dalam Bina Damai: Pengalaman La Rimpu (Sekolah Rintisan Perempuan untuk Perubahan) di Bima, Nusa Tenggara Barat - Wardatun, Atun; Wahid, Abdul (UIN Sunan Kudus, 2021)
The study considerately challenges several stereotypes regarding women as victims in conflicts and their condemnatory identity as sources of defamation and social instabilities. Regardless of numerous alternative perspectives concerning women and peace, critical investigations by creative measures utilizing local values to promote security and tranquillity while promoting women's roles in society are limited. This paper investigates the approaches and methods of la Rimpu (a women-initiated school for changes) in chronic conflicts of neighbouring villages in Bima, West Nusa Tenggara, and their beneficial impacts. By combining an auto-ethnographic method, intensive participatory observations, in-depth interviews with women with experiences in la Rimpu, and document analyses, this article argues that revitalizing and integrating local values to foster peace and prevent conflicts alternate a reasonable and effective strategy for two main reasons namely building women's confidence in advocating the issues and preventing refusal from the natives. Local values are considered as a crucial cultural capital strengthening their identity and social solidarity.